PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DENGAN MENGGUNAKAN MEDIA GAMBAR - Martinis, Martinis (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research aim was to describe for improve learning achievement  comparison and scale with Media Gambar at the primary school ini 22 Baduih Simawang. The study was a classroom action research consisting of two cycles. Each cycles consisted of planning, action, observation, relection. The data analyzed by using qualitative and quantitative approach.The research subject  at class student IV  SD Negeri22 baduih Simawang with 25 students. The result of the research showed improve learning achievement with Media Gambar Kata Kunci : hasil belajar ; pembelajaran pendidikan kewarganegaraan : media gambar